Regular and Young Investigator Award Abstracts 2020
DOI: 10.1136/jitc-2020-sitc2020.0245
|View full text |Cite
|
Sign up to set email alerts
|

245 Human TLR8 knock-in mice potentiate immunotherapy responses of MC38 syngeneic tumors

Abstract: BackgroundToll-like receptors (TLRs) serve critical roles in mediating innate immune responses against many pathogens. However, they may also bind to endogenous ligands and lead to the pathogenesis of autoimmunity. Although TLR8 belongs to the same TLR family as TLR7, its role in inflammation and tumor progression is not yet fully understood due to the lack of suitable animal models. In humans, both TLR7 and TLR8 recognize single-stranded self-RNA, viral RNA, and synthetic small molecule agonists.1, 2 However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Shanshan Qi et al. ( 223 ) generated hTLR8 mice by replacing exon 3 of mouse Tlr8 with human TLR8 to analyze the role of TLR8 in tumor progression. They found that the MC38 tumor grew slower in hTLR8 mice compared with naïve mice.…”
Section: Tlr-mediated Immunity In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Shanshan Qi et al. ( 223 ) generated hTLR8 mice by replacing exon 3 of mouse Tlr8 with human TLR8 to analyze the role of TLR8 in tumor progression. They found that the MC38 tumor grew slower in hTLR8 mice compared with naïve mice.…”
Section: Tlr-mediated Immunity In Cancermentioning
confidence: 99%
“…They found that the MC38 tumor grew slower in hTLR8 mice compared with naïve mice. hTLR8 mice also exhibit increased IFN-γ and TNF-α positive CD4 + T cells and effector T cells ( 223 ).…”
Section: Tlr-mediated Immunity In Cancermentioning
confidence: 99%